Nfluence of technological factors on the properties of concrete mix and concrete - Urinbek Turgunbaev; Bobur Toxirov (International Journal on Orange Technologies, 2021)
The article studies the influence of technological factors on the properties of concrete mix and concrete, calculates the compositions of concrete by the calculation and experimental method, determines the compressive strength of concrete from the method of introducing the chemical additive KJ-3, as well as the effect of cement consumption on the strength of concrete with the addition of KJ-3.